Two potential mechanisms of oxaliplatin-induced haemolytic anaemia in a single patient - Hofheinz, Ralf-Dieter; Nguyen, Xuan-Duc; Buchheidt, Dieter; Kerowgan, Mohammed; Hehlmann, Rüdiger; Hochhaus, Andreas (Cancer chemotherapy and pharmacology, 2004)
Only two patients with adequately documented oxaliplatin-induced autoimmune haemolytic anaemia have previously been reported. We report here a third patient with an immune-haematological finding favouring a bispecific mechanism (immune-complex and penicillin type) of oxaliplatin-induced haemolysis.